Automatic Texture analysis of cartilage for early detection of osteoarthritis (International Journal of Engineering and Computer Science, 2017)
Osteoarthritis (OA) is the most commonly occurring chronic disease affecting elder population. OA characterized by the degenerative change in the knee cartilage. Early detection of OA will be very useful for medical treatments. Osteoarthritis symptoms are swelling, loss of movement, severe pain, decrease in the function of the joint. This work is to segment the cartilage automatically from the knee MRI. Texture algorithm applied on the segmented cartilage region. This is checking the biochemical properties of the cartilage. The fluid content in cartilage region increases with Joint Space Width (JSW).Micro texture descriptors (MTD) algorithms are used for the texture analysis.